IMPLEMENTATION OF SOUL MARKETING BASED ISLAMIC RELIGIOUS EDUCATION AT PT ASURANSI TAKAFUL KELUARGA JAKARTA - Masyhurul Khamis; Saeful Anwar; Ibdalsyah Ibdalsyah (AMWALUNA (Jurnal Ekonomi dan Keuangan Syariah), 2022)
The purpose of this study is to analyze the implementation of the Islamic company's HR development model (soul marketing) based on Islamic religious education for marketers at PT Asuransi Takaful Keluarga Jakarta. Research using qualitative research methods is motivated by the spiritual strength of marketing at PT Asuransi Takaful Keluarga Jakarta which attracts the attention of the author to examine why marketers can survive even though their income is not like marketers' income in conventional insurance. The results of this study indicate that the implementation of soul marketing-based Islamic religious education at PT Asuransi Takaful Keluarga Jakarta is to make marketers sincere and not market fraudulently as taught by the Prophet in doing business, as well as building mental awareness in daily life in Takaful, among others Every morning, perform dhuha prayers while adhering to the Covid-19 protocol, then proceed with the tadarrus of the al-Qur'an surah Al-Waqi'ah, Al-Mulk and Ar-Rahman. Soul marketing, is a formula that focuses on individuals who carry out marketing strategies with honesty, sincerity, professionalism, friendship and generosity. Honesty generates trust, sincerity and high dedication, sincerity generates calm at work, professionals give birth to maximum efforts that satisfy consumers, friendship forms networks and unlimited moral and material benefits. Based on a generous attitude and the sustainable workings of all these elements will form an ideal mindset and practice. Although soul marketing is not a practical solution that can go through without a process. After marketing soul becomes the basis of the mindset of a marketer, it will form the basis of the company's movement and become the core of the implementation of the marketing strategy that will be carried out. If it has been implemented on an ongoing basis, the concept of soul marketing can become a marketing morality for marketers. And this is the essence of Islamic religious education itself.